A survivability analysis of enterprise hard drives incorporating the impact of workload - Mallik, Aman; Reddy, B Ranjith; Sahoo, Gadadhar (Frontiers in Computer Science, 2024)
One major reason for downtime in enterprise storage systems is hard disk drive (HDD) failure. Current research indicates that the data access rate has a significant impact on the survival probability of HDDs. In this paper, a model is proposed to estimate the probability of HDD failure based on the total data (TD) read or written as well as the average access rate (AAR) for a given drive model. The results of case studies based on an HDD failure dataset validate the efficacy of the proposed approach of using a storage controller to improve throttle commands to disks to minimize the failure risk.